Preparedness of Countries in Preventing Monkeypox in the Upcoming Mass Gathering Events: Status and Recommendations - AlSamhori, Ahmad; AlSamhori, Jehad; Alkhawaldeh, Ibraheem; AlSamhori, Abdelrahman (Jordan Medical Journal, 2024)
A dangerous zoonotic illness call monkeypox (MPX) is endangering public health by spreading around the world. It is endemic to western and central Africa, particularly in the Democratic Republic of the Congo, where it was first reported in a human being. Concern is raised by the recent increase of incidence across several continents in non-endemic nations. Thus, there are 86746 confirmed cases as of 31 March 2023. MPX cases are significantly rising, with males seeing the highest rates of infection. Concise recommendations by World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC) should be considered towards mass gatherings events(MG) to reduce the spreading of this disease. Football leagues and other sport matches, which attract a very large number of participants and audience, impose serious risks and public health consequences. Thus, with the beginning of vaccinations in July 2022, globally healthcare policymakers must make a difficult choice about the monkeypox vaccine at this point in the disease's progression. Since, CDC recommends that healthcare practitioners establish clinical guidelines that will help them recognize instances and give the appropriate monitoring, follow-up, and treatment updates. In the current global outbreak, gay, bisexual, and other men who have sex with men (MSM) are the most impacted demographic group. Therefore, it is essential to curb the spread of the monkeypox virus by increasing vaccine demand among local LGBTQIA+ community members and educating them about the value of immunization.